Impact of preoperative frailty on new disability or death after cardiac surgery in elderly patients: a prospective cohort study - Ma, Wenwen; Shui, Weikang; Peng, Qian; Zhu, Chaoyang; Zhao, Wenjing; Fan, Guanglei; Zhu, Shanshan (Frontiers in Medicine, 2025)
BackgroundDisability may be a potential adverse outcome of exposure to stressors in frail patients, and assessment of frailty may provide additional information for preoperative decision-making, but there is a lack of research on the impact of preoperative frailty on death or new disability after cardiac surgery. The main objective of this study was to evaluate the effect of preoperative frailty on short-term death or new disability after cardiac surgery in elderly individuals.Patients and methodsThis prospective cohort study included 351 patients aged ≥60 years who were scheduled to undergo elective open heart surgery at the Affiliated Hospital of Xuzhou Medical University from March 2023 to March 2024. Patients were examined prospectively using the Comprehensive Assessment of Frailty (CAF) score, which separated patients into frail and non-frail groups. The primary outcome was 90-day disability or death. Multivariate logistic regression models were used to estimate the association between frailty and 90-day new disability or death.ResultsAn assessment of frailty was performed on 351 patients, and 325 patients were included in the final analysis. The prevalence of frailty was found to be 23.08%. New disability or death occurred within 90 days after surgery in 41 (12.6%) of our patients. In multivariate analysis, frailty [OR, 3.31; 95% CI, 1.43–7.62] was independently associated with 90-day new disability or death. Empirical ROC analysis showed that CAF (AUC = 0.762) predicted 90-day new disability or death postoperatively more reliably than the traditional risk assessment tools ASA + age (AUC = 0.656) and EuroSCORE II (AUC = 0.643).ConclusionThe study demonstrates that preoperative frailty, bypass time, diabetes, BMI and EuroSCORE II are independent risk factors for 90-day new disability or death after cardiac surgery in elderly patients. Notably, frailty was a more effective predictor of 90-day new disability or death than the traditional risk predictors EuroSCORE II and ASA + age.